O programa brasileiro de patentes verdes: uma análise à luz da complexidade ambiental e da sustentabilidade - Costenaro, João Pedro do Nascimento (2023)
The contemporary environmental crisis requires an energetic response from society, which, combined with current way of thinking, strongly influenced by a predatory and universalist logic, permeates the current mode of unsustainable development. In this scenario, industrial property plays a leading role in promoting sustainability. Thus, industrial patents, especially green patents, which are characterized as instruments for the protection of environmentally friendly inventions, deserve an analysis under the prism of environmental complexity, since they combine innovation, technology and environment. In this sense, it is questioned to what extent the brazilian green patent program, in the light of environmental complexity, implies the promotion of sustainable technologies. The adopted methodology will be based on the quadrinomial: basic theory, method of approach, method of procedure and research technique. As a base theory, a systemic-complex orientation was adopted, using the theoretical bases of Edgar Morin and Enrique Leff. As a method of procedure, bibliographical research and documental analysis were used. In turn, as a research technique, reviews, records and data collection were used. The research was divided into two chapters, each with three subdivisions. The first chapter aims to present the theoretical-normative framework of industrial property and the brazilian green patent program, helping to understand the instruments for protecting industrial property so that, in the end, the brazilian patent program can be analyzed. The second, based on the knowledge and observations raised in the previous chapter, will aim to uncover the environmental complexity and sustainability behind the idea of the brazilian green patent program, so that it will discuss whether it is possible to overcome the cartesian model of predatory technology via the brazilian program of green patents. Through the research carried out, it is concluded that the symbiotic construction of a relationship between technology and nature remains imperative, derived from the need to preserve biodiversity without harming technological innovation. The brazilian green patent program emerges as a result of the process through which nature and technology, glimpsed at first on opposite sides, can be observed from the prism of environmental complexity and used in the promotion of sustainability.